Gel Carriers for Plant Extracts and Synthetic Pesticides in Rodent and Arthropod Pest Control: An Overview - Shah, Jawad Ali; Vendl, Tomas; Aulicky, Radek; Frankova, Marcela; Stejskal, Vaclav (Gels (Basel, Switzerland), 2022)
Insecticides and rodenticides form the basis of integrated pest management systems worldwide. As pest resistance continues to increase and entire groups of chemical active ingredients are restricted or banned, manufacturers are looking for new options for more effective formulations and safer application methods for the remaining pesticide ingredients. In addition to new technological adaptations of mainstream formulations in the form of sprays, fumigants, and dusts, the use of gel formulations is becoming increasingly explored and employed. This article summarizes information on the current and potential use of gel (including hydrogel) and paste formulations against harmful arthropods or rodents in specific branches of pest management in the agricultural, food, stored product, structural wood, urban, medical, and public health areas. Due to the worldwide high interest in natural substances, part of the review was devoted to the use of gels for the formulation of pesticide substances of botanical origin, such as essential or edible oils. Gels as emerging formulation of so called "smart insecticides" based on molecular iRNA disruptors are discussed.
Keywords: nanotechnology; rodenticides; essential oils; integrated pest management; polymers; formulations; vector control; plant extracts; insecticides; hydrogels